Infections With Enterohepatic Non-H. pylori Helicobacter Species in X-Linked Agammaglobulinemia: Clinical Cases and Review of the Literature - Romo-Gonzalez, Carolina; Bustamante-Ogando, Juan Carlos; Yamazaki-Nakashimada, Marco Antonio; Aviles-Jimenez, Francisco; Otero-Mendoza, Francisco; Espinosa-Rosales, Francisco Javier; Espinosa-Padilla, Sara Elva; Scheffler Mendoza, Selma Cecilia; Durán-McKinster, Carola; García-Romero, Maria Teresa; Saez-de-Ocariz, Marimar; Lopez-Herrera, Gabriela (Frontiers in Cellular and Infection Microbiology, 2022)
The genus Helicobacter is classified into two main groups according to its habitat: gastric and enterohepatic. Patients with X-linked agammaglobulinemia (XLA) appear to be associated with invasive infection with enterohepatic non-Helicobacter pylori species (NHPH), mainly H. cinaedi and H. bilis. Such infections are difficult to control and have a high potential for recurrence. The spectrum of illnesses caused by these species includes recurrent fever, bacteremia, arthritis, osteomyelitis, cellulitis, abdominal abscesses, and pyoderma gangrenosum-like ulcer. The presence of these Helicobacters is particularly difficult to diagnose and eradicate, as they are very fastidious bacteria and present resistance to several types of antibiotics. We report two clinical cases of XLA patients infected with H. bilis. These infections were chronic in these patients and could not be eradicated in one of them. We also review the cases of enterohepatic non-Helicobacter pylori species (NHPH) in patients with this inborn error of immunity.